Mengubah Kinerja Dosen: Peran Mediasi Kepemimpinan Melayani dalam Meningkatkan Kompetensi Digital dan Kesejahteraan Psikologis - Hengky Kosasih; Susanto Susanto; Ahmad Fadli; Erina Alimin; Siti Alhamra Salqaura (Society, 2024)
Lecturer performance is a critical factor in improving the quality of higher education. This study investigates the impact of digital competence and psychological well-being on lecturer performance, with servant leadership as a mediating variable. A quantitative methodology was employed, collecting data through structured questionnaires distributed to lecturers at several private universities in Medan City. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results reveal that digital competence and psychological well-being positively and significantly affect lecturer performance. Additionally, servant leadership mediates the relationship between these independent variables and lecturer performance, highlighting its essential role in enhancing lecturers’ digital readiness and psychological well-being. This study contributes to the theoretical framework by integrating leadership theory with individual attributes (competence and well-being) to examine their influence on lecturer performance in higher education. The findings emphasize the importance of adopting servant leadership to improve lecturer performance by fostering digital competence and promoting psychological well-being.